CN106410159B - 一种聚苯胺凝胶包覆锡铜纳米管复合材料的制备方法 - Google Patents
一种聚苯胺凝胶包覆锡铜纳米管复合材料的制备方法 Download PDFInfo
- Publication number
- CN106410159B CN106410159B CN201610983553.2A CN201610983553A CN106410159B CN 106410159 B CN106410159 B CN 106410159B CN 201610983553 A CN201610983553 A CN 201610983553A CN 106410159 B CN106410159 B CN 106410159B
- Authority
- CN
- China
- Prior art keywords
- tin
- solution
- copper
- gel
- reaction
- Prior art date
- Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
- Active
Links
- KUNSUQLRTQLHQQ-UHFFFAOYSA-N copper tin Chemical compound [Cu].[Sn] KUNSUQLRTQLHQQ-UHFFFAOYSA-N 0.000 title claims abstract description 52
- 239000002071 nanotube Substances 0.000 title claims abstract description 49
- 229920000767 polyaniline Polymers 0.000 title claims abstract description 32
- 239000002131 composite material Substances 0.000 title claims abstract description 23
- 238000002360 preparation method Methods 0.000 title claims abstract description 7
- ATJFFYVFTNAWJD-UHFFFAOYSA-N Tin Chemical compound [Sn] ATJFFYVFTNAWJD-UHFFFAOYSA-N 0.000 claims abstract description 21
- 238000000034 method Methods 0.000 claims abstract description 20
- 238000005253 cladding Methods 0.000 claims abstract 2
- 239000008367 deionised water Substances 0.000 claims description 25
- 229910021641 deionized water Inorganic materials 0.000 claims description 25
- XLYOFNOQVPJJNP-UHFFFAOYSA-N water Chemical compound O XLYOFNOQVPJJNP-UHFFFAOYSA-N 0.000 claims description 25
- 238000006243 chemical reaction Methods 0.000 claims description 23
- 238000003756 stirring Methods 0.000 claims description 19
- ROOXNKNUYICQNP-UHFFFAOYSA-N ammonium persulfate Chemical compound [NH4+].[NH4+].[O-]S(=O)(=O)OOS([O-])(=O)=O ROOXNKNUYICQNP-UHFFFAOYSA-N 0.000 claims description 18
- PAYRUJLWNCNPSJ-UHFFFAOYSA-N Aniline Chemical compound NC1=CC=CC=C1 PAYRUJLWNCNPSJ-UHFFFAOYSA-N 0.000 claims description 14
- 239000000126 substance Substances 0.000 claims description 13
- LFQSCWFLJHTTHZ-UHFFFAOYSA-N Ethanol Chemical compound CCO LFQSCWFLJHTTHZ-UHFFFAOYSA-N 0.000 claims description 12
- 229910021627 Tin(IV) chloride Inorganic materials 0.000 claims description 11
- HPGGPRDJHPYFRM-UHFFFAOYSA-J tin(iv) chloride Chemical compound Cl[Sn](Cl)(Cl)Cl HPGGPRDJHPYFRM-UHFFFAOYSA-J 0.000 claims description 11
- 229910001870 ammonium persulfate Inorganic materials 0.000 claims description 9
- ORTQZVOHEJQUHG-UHFFFAOYSA-L copper(II) chloride Chemical compound Cl[Cu]Cl ORTQZVOHEJQUHG-UHFFFAOYSA-L 0.000 claims description 7
- 239000000178 monomer Substances 0.000 claims description 7
- 239000012279 sodium borohydride Substances 0.000 claims description 7
- 229910000033 sodium borohydride Inorganic materials 0.000 claims description 7
- XWULEGJMNMPRCI-UHFFFAOYSA-N [bis(phosphonooxymethyl)amino]methyl dihydrogen phosphate Chemical compound OP(O)(=O)OCN(COP(O)(O)=O)COP(O)(O)=O XWULEGJMNMPRCI-UHFFFAOYSA-N 0.000 claims description 5
- 239000012467 final product Substances 0.000 claims description 5
- 238000003760 magnetic stirring Methods 0.000 claims description 5
- 239000005457 ice water Substances 0.000 claims description 4
- 238000001035 drying Methods 0.000 claims 2
- NJSSICCENMLTKO-HRCBOCMUSA-N [(1r,2s,4r,5r)-3-hydroxy-4-(4-methylphenyl)sulfonyloxy-6,8-dioxabicyclo[3.2.1]octan-2-yl] 4-methylbenzenesulfonate Chemical compound C1=CC(C)=CC=C1S(=O)(=O)O[C@H]1C(O)[C@@H](OS(=O)(=O)C=2C=CC(C)=CC=2)[C@@H]2OC[C@H]1O2 NJSSICCENMLTKO-HRCBOCMUSA-N 0.000 claims 1
- 238000013019 agitation Methods 0.000 claims 1
- 238000004090 dissolution Methods 0.000 claims 1
- 238000002156 mixing Methods 0.000 claims 1
- HBBGRARXTFLTSG-UHFFFAOYSA-N Lithium ion Chemical compound [Li+] HBBGRARXTFLTSG-UHFFFAOYSA-N 0.000 abstract description 21
- 229910001416 lithium ion Inorganic materials 0.000 abstract description 21
- 229920001940 conductive polymer Polymers 0.000 abstract description 11
- 239000007772 electrode material Substances 0.000 abstract description 10
- 238000011065 in-situ storage Methods 0.000 abstract description 7
- 239000000463 material Substances 0.000 abstract description 7
- 239000003638 chemical reducing agent Substances 0.000 abstract description 6
- 238000007599 discharging Methods 0.000 abstract description 6
- 238000011549 displacement method Methods 0.000 abstract description 6
- 238000006722 reduction reaction Methods 0.000 abstract description 6
- 230000008569 process Effects 0.000 abstract description 5
- RYGMFSIKBFXOCR-UHFFFAOYSA-N Copper Chemical compound [Cu] RYGMFSIKBFXOCR-UHFFFAOYSA-N 0.000 abstract description 3
- 239000011159 matrix material Substances 0.000 abstract description 2
- 229910052802 copper Inorganic materials 0.000 abstract 1
- 239000010949 copper Substances 0.000 abstract 1
- 230000000379 polymerizing effect Effects 0.000 abstract 1
- 239000000243 solution Substances 0.000 description 47
- 239000000499 gel Substances 0.000 description 30
- 239000007773 negative electrode material Substances 0.000 description 10
- 239000010405 anode material Substances 0.000 description 8
- 239000000047 product Substances 0.000 description 8
- 229920000371 poly(diallyldimethylammonium chloride) polymer Polymers 0.000 description 7
- 238000005406 washing Methods 0.000 description 7
- 238000005119 centrifugation Methods 0.000 description 6
- 239000012535 impurity Substances 0.000 description 6
- 238000006116 polymerization reaction Methods 0.000 description 6
- 238000001291 vacuum drying Methods 0.000 description 6
- 238000005054 agglomeration Methods 0.000 description 4
- 230000002776 aggregation Effects 0.000 description 4
- 230000005540 biological transmission Effects 0.000 description 4
- 239000006258 conductive agent Substances 0.000 description 4
- 238000006073 displacement reaction Methods 0.000 description 4
- 239000011149 active material Substances 0.000 description 3
- 239000011230 binding agent Substances 0.000 description 3
- 238000004140 cleaning Methods 0.000 description 3
- 238000009792 diffusion process Methods 0.000 description 3
- 239000003792 electrolyte Substances 0.000 description 3
- 239000002184 metal Substances 0.000 description 3
- 229910052751 metal Inorganic materials 0.000 description 3
- 239000002086 nanomaterial Substances 0.000 description 3
- YGNWFPQDHGQKIM-UHFFFAOYSA-N (1,3-dioxo-2,4,8,9-tetraoxa-6-aza-1lambda5,3lambda5-diphosphabicyclo[4.2.2]decan-3-yl) dihydrogen phosphate Chemical compound C1N2COP(=O)(O1)OP(=O)(OC2)OP(=O)(O)O YGNWFPQDHGQKIM-UHFFFAOYSA-N 0.000 description 2
- WHXSMMKQMYFTQS-UHFFFAOYSA-N Lithium Chemical compound [Li] WHXSMMKQMYFTQS-UHFFFAOYSA-N 0.000 description 2
- 239000011889 copper foil Substances 0.000 description 2
- 238000000840 electrochemical analysis Methods 0.000 description 2
- 229910052744 lithium Inorganic materials 0.000 description 2
- 239000011148 porous material Substances 0.000 description 2
- 230000002441 reversible effect Effects 0.000 description 2
- QGZKDVFQNNGYKY-UHFFFAOYSA-O Ammonium Chemical compound [NH4+] QGZKDVFQNNGYKY-UHFFFAOYSA-O 0.000 description 1
- OKTJSMMVPCPJKN-UHFFFAOYSA-N Carbon Chemical compound [C] OKTJSMMVPCPJKN-UHFFFAOYSA-N 0.000 description 1
- 229910001290 LiPF6 Inorganic materials 0.000 description 1
- 238000003917 TEM image Methods 0.000 description 1
- 239000013543 active substance Substances 0.000 description 1
- 239000000872 buffer Substances 0.000 description 1
- 239000011248 coating agent Substances 0.000 description 1
- 239000011247 coating layer Substances 0.000 description 1
- 238000000576 coating method Methods 0.000 description 1
- 239000002322 conducting polymer Substances 0.000 description 1
- 230000006378 damage Effects 0.000 description 1
- 238000009831 deintercalation Methods 0.000 description 1
- 230000000694 effects Effects 0.000 description 1
- 238000002848 electrochemical method Methods 0.000 description 1
- 239000008151 electrolyte solution Substances 0.000 description 1
- 238000004146 energy storage Methods 0.000 description 1
- 230000002708 enhancing effect Effects 0.000 description 1
- 229910002804 graphite Inorganic materials 0.000 description 1
- 239000010439 graphite Substances 0.000 description 1
- 239000011796 hollow space material Substances 0.000 description 1
- 230000003993 interaction Effects 0.000 description 1
- 238000009830 intercalation Methods 0.000 description 1
- 230000002687 intercalation Effects 0.000 description 1
- 230000003446 memory effect Effects 0.000 description 1
- 229910044991 metal oxide Inorganic materials 0.000 description 1
- 150000004706 metal oxides Chemical class 0.000 description 1
- 150000002739 metals Chemical class 0.000 description 1
- 238000001000 micrograph Methods 0.000 description 1
- 239000000203 mixture Substances 0.000 description 1
- 150000004968 peroxymonosulfuric acids Chemical class 0.000 description 1
- 239000002861 polymer material Substances 0.000 description 1
- 229920000128 polypyrrole Polymers 0.000 description 1
- 229920000123 polythiophene Polymers 0.000 description 1
- 239000002994 raw material Substances 0.000 description 1
- 238000006467 substitution reaction Methods 0.000 description 1
- 238000012360 testing method Methods 0.000 description 1
- 239000011366 tin-based material Substances 0.000 description 1
- 230000009466 transformation Effects 0.000 description 1
- 238000000844 transformation Methods 0.000 description 1
- 238000005303 weighing Methods 0.000 description 1
Classifications
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M4/00—Electrodes
- H01M4/02—Electrodes composed of, or comprising, active material
- H01M4/36—Selection of substances as active materials, active masses, active liquids
- H01M4/362—Composites
- H01M4/366—Composites as layered products
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B82—NANOTECHNOLOGY
- B82Y—SPECIFIC USES OR APPLICATIONS OF NANOSTRUCTURES; MEASUREMENT OR ANALYSIS OF NANOSTRUCTURES; MANUFACTURE OR TREATMENT OF NANOSTRUCTURES
- B82Y30/00—Nanotechnology for materials or surface science, e.g. nanocomposites
-
- B—PERFORMING OPERATIONS; TRANSPORTING
- B82—NANOTECHNOLOGY
- B82Y—SPECIFIC USES OR APPLICATIONS OF NANOSTRUCTURES; MEASUREMENT OR ANALYSIS OF NANOSTRUCTURES; MANUFACTURE OR TREATMENT OF NANOSTRUCTURES
- B82Y40/00—Manufacture or treatment of nanostructures
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M10/00—Secondary cells; Manufacture thereof
- H01M10/05—Accumulators with non-aqueous electrolyte
- H01M10/052—Li-accumulators
- H01M10/0525—Rocking-chair batteries, i.e. batteries with lithium insertion or intercalation in both electrodes; Lithium-ion batteries
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M4/00—Electrodes
- H01M4/02—Electrodes composed of, or comprising, active material
- H01M4/36—Selection of substances as active materials, active masses, active liquids
- H01M4/38—Selection of substances as active materials, active masses, active liquids of elements or alloys
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M4/00—Electrodes
- H01M4/02—Electrodes composed of, or comprising, active material
- H01M4/36—Selection of substances as active materials, active masses, active liquids
- H01M4/38—Selection of substances as active materials, active masses, active liquids of elements or alloys
- H01M4/387—Tin or alloys based on tin
-
- H—ELECTRICITY
- H01—ELECTRIC ELEMENTS
- H01M—PROCESSES OR MEANS, e.g. BATTERIES, FOR THE DIRECT CONVERSION OF CHEMICAL ENERGY INTO ELECTRICAL ENERGY
- H01M4/00—Electrodes
- H01M4/02—Electrodes composed of, or comprising, active material
- H01M4/36—Selection of substances as active materials, active masses, active liquids
- H01M4/60—Selection of substances as active materials, active masses, active liquids of organic compounds
- H01M4/602—Polymers
- H01M4/606—Polymers containing aromatic main chain polymers
-
- Y—GENERAL TAGGING OF NEW TECHNOLOGICAL DEVELOPMENTS; GENERAL TAGGING OF CROSS-SECTIONAL TECHNOLOGIES SPANNING OVER SEVERAL SECTIONS OF THE IPC; TECHNICAL SUBJECTS COVERED BY FORMER USPC CROSS-REFERENCE ART COLLECTIONS [XRACs] AND DIGESTS
- Y02—TECHNOLOGIES OR APPLICATIONS FOR MITIGATION OR ADAPTATION AGAINST CLIMATE CHANGE
- Y02E—REDUCTION OF GREENHOUSE GAS [GHG] EMISSIONS, RELATED TO ENERGY GENERATION, TRANSMISSION OR DISTRIBUTION
- Y02E60/00—Enabling technologies; Technologies with a potential or indirect contribution to GHG emissions mitigation
- Y02E60/10—Energy storage using batteries
Landscapes
- Chemical & Material Sciences (AREA)
- Engineering & Computer Science (AREA)
- Chemical Kinetics & Catalysis (AREA)
- Electrochemistry (AREA)
- General Chemical & Material Sciences (AREA)
- Nanotechnology (AREA)
- Composite Materials (AREA)
- General Physics & Mathematics (AREA)
- Condensed Matter Physics & Semiconductors (AREA)
- Manufacturing & Machinery (AREA)
- Crystallography & Structural Chemistry (AREA)
- Physics & Mathematics (AREA)
- Materials Engineering (AREA)
- Battery Electrode And Active Subsutance (AREA)
- Macromolecular Compounds Obtained By Forming Nitrogen-Containing Linkages In General (AREA)
- Secondary Cells (AREA)
Abstract
Description
Claims (5)
Priority Applications (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201610983553.2A CN106410159B (zh) | 2016-11-09 | 2016-11-09 | 一种聚苯胺凝胶包覆锡铜纳米管复合材料的制备方法 |
Applications Claiming Priority (1)
| Application Number | Priority Date | Filing Date | Title |
|---|---|---|---|
| CN201610983553.2A CN106410159B (zh) | 2016-11-09 | 2016-11-09 | 一种聚苯胺凝胶包覆锡铜纳米管复合材料的制备方法 |
Publications (2)
| Publication Number | Publication Date |
|---|---|
| CN106410159A CN106410159A (zh) | 2017-02-15 |
| CN106410159B true CN106410159B (zh) | 2019-07-19 |
Family
ID=58015352
Family Applications (1)
| Application Number | Title | Priority Date | Filing Date |
|---|---|---|---|
| CN201610983553.2A Active CN106410159B (zh) | 2016-11-09 | 2016-11-09 | 一种聚苯胺凝胶包覆锡铜纳米管复合材料的制备方法 |
Country Status (1)
| Country | Link |
|---|---|
| CN (1) | CN106410159B (zh) |
Families Citing this family (2)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN108206285B (zh) | 2017-12-12 | 2021-08-24 | 中国科学院物理研究所 | 一种复合包覆的纳米锡负极材料及其制备方法和应用 |
| CN119786571B (zh) * | 2024-12-30 | 2026-01-16 | 远景动力技术(江苏)有限公司 | 一种负极材料及其制备方法、负极极片和锂离子电池 |
Citations (2)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN102244254A (zh) * | 2011-06-17 | 2011-11-16 | 天津大学 | 一种中空纳米线-聚合物膜核壳结构复合材料及其制备方法 |
| CN105295038A (zh) * | 2015-11-05 | 2016-02-03 | 天津大学 | 导电聚苯胺凝胶的制备方法及其在超级电容器中的应用 |
-
2016
- 2016-11-09 CN CN201610983553.2A patent/CN106410159B/zh active Active
Patent Citations (2)
| Publication number | Priority date | Publication date | Assignee | Title |
|---|---|---|---|---|
| CN102244254A (zh) * | 2011-06-17 | 2011-11-16 | 天津大学 | 一种中空纳米线-聚合物膜核壳结构复合材料及其制备方法 |
| CN105295038A (zh) * | 2015-11-05 | 2016-02-03 | 天津大学 | 导电聚苯胺凝胶的制备方法及其在超级电容器中的应用 |
Non-Patent Citations (2)
| Title |
|---|
| Solvothermal synthesis of carbon-coated tin nanorods for superior reversible lithium ion storage;Ping Wu 等;《Materials Research Bulletin》;20110906;第46卷;第2278-2282页 |
| 锡/聚吡咯三维纳米结构锂离子电池负极材料的制备及稳定性研究;范欣;《万方数据知识服务平台》;20151203 |
Also Published As
| Publication number | Publication date |
|---|---|
| CN106410159A (zh) | 2017-02-15 |
Similar Documents
| Publication | Publication Date | Title |
|---|---|---|
| Li et al. | Sphere-like SnO2/TiO2 composites as high-performance anodes for lithium ion batteries | |
| CN104617281B (zh) | 一种钠离子电池锑/掺氮碳纳米片负极复合材料的制备方法 | |
| CN103346303A (zh) | 一种硅碳复合材料及其制备方法、锂离子电池 | |
| Li et al. | Architecture and performance of Si/C microspheres assembled by nano-Si via electro-spray technology as stability-enhanced anodes for lithium-ion batteries | |
| CN109786711B (zh) | 一种多孔碳骨架包覆锡复合电极材料的制备方法 | |
| CN107634210B (zh) | 一种高性能的锂/钠电池负极材料及其制备方法 | |
| CN106784714A (zh) | 一种锂离子电池硅基复合负极材料及其制备方法 | |
| CN101593825B (zh) | 锂离子电池纳米锑/石墨纳米片复合材料负极及其制备方法 | |
| CN109873149B (zh) | 二硫化钼和双碳层共修饰的硫化亚锡纳米球及其制备方法 | |
| Zhang et al. | Paradigm metallothermic-sulfidation-carbonization constructing ZIFs-derived TMSs@ Graphene/CNx heterostructures for high-capacity and long-life energy storage | |
| Li et al. | Ultrafine Sb2S3@ carbon-nanofibers for fast and stable sodium storage | |
| CN115000366B (zh) | 具有核壳结构的柔性自支撑锂硫电池正极薄膜及制备方法 | |
| CN106229514B (zh) | 石墨烯改性导电聚合物凝胶包覆金属纳米颗粒的制备方法与应用 | |
| CN114023948B (zh) | 硅碳负极材料及其制备方法、锂离子电池 | |
| Yu et al. | High performance of porous silicon/carbon/RGO network derived from rice husks as anodes for lithium-ion batteries | |
| Mo et al. | 3D holey-graphene frameworks cross-linked with encapsulated mesoporous amorphous FePO4 nanoparticles for high-power lithium-ion batteries | |
| Wang et al. | Carbon-coated SnO2@ carbon nanofibers produced by electrospinning-electrospraying method for anode materials of lithium-ion batteries | |
| Zhang et al. | Novel Si@ C/P anode materials with improved cyclability and rate capacity for lithium-ion batteries | |
| CN105552302A (zh) | 一种可折叠硫正极复合电极结构 | |
| CN111313012A (zh) | 多壁碳纳米管石墨锂离子电池负极材料及其制备方法 | |
| Guo et al. | Carbon/polymer bilayer-coated Si-SiO x electrodes with enhanced electrical conductivity and structural stability | |
| CN105226244A (zh) | 三维多孔硅-纳米银复合材料及其制备和作为锂离子电池负极材料的应用 | |
| Xu et al. | Unraveling the mechanism on improved kinetics performance of sulfurized polyacrylonitrile with defective conductive carbon matrix | |
| CN109768260A (zh) | 一种磷化二钴/碳复合材料及其制备方法和用途 | |
| CN108199020A (zh) | 一种碳包覆微纳层次结构硅负极材料及其制备方法和应用 |
Legal Events
| Date | Code | Title | Description |
|---|---|---|---|
| C06 | Publication | ||
| PB01 | Publication | ||
| C10 | Entry into substantive examination | ||
| SE01 | Entry into force of request for substantive examination | ||
| GR01 | Patent grant | ||
| GR01 | Patent grant | ||
| TR01 | Transfer of patent right | ||
| TR01 | Transfer of patent right |
Effective date of registration: 20220329 Address after: 300304 room 1-2050, Block E, No. 6, Huafeng Road, Huaming high tech Industrial Zone, Dongli District, Tianjin Patentee after: Zhongzhi online Co.,Ltd. Address before: 300072 Tianjin City, Nankai District Wei Jin Road No. 92, Tianjin University Patentee before: Tianjin University |
|
| TR01 | Transfer of patent right |
Effective date of registration: 20221019 Address after: Room 107, Building 6, No. 91, Fahuasi Street, Dongcheng District, Beijing 100062 Patentee after: Beijing Legend Yousheng Culture Media Co.,Ltd. Address before: 300304 room 1-2050, Block E, No. 6, Huafeng Road, Huaming high tech Industrial Zone, Dongli District, Tianjin Patentee before: Zhongzhi online Co.,Ltd. |
|
| TR01 | Transfer of patent right | ||
| EE01 | Entry into force of recordation of patent licensing contract |
Application publication date: 20170215 Assignee: Tianjin aisida New Material Technology Co.,Ltd. Assignor: Beijing Legend Yousheng Culture Media Co.,Ltd. Contract record no.: X2023980040791 Denomination of invention: A preparation method of polyaniline gel coated tin copper nanotube composite Granted publication date: 20190719 License type: Common License Record date: 20230829 |
|
| EE01 | Entry into force of recordation of patent licensing contract | ||
| EE01 | Entry into force of recordation of patent licensing contract |
Application publication date: 20170215 Assignee: TIANJIN ZHUJIN TECHNOLOGY DEVELOPMENT Corp. Assignor: Beijing Legend Yousheng Culture Media Co.,Ltd. Contract record no.: X2024980004064 Denomination of invention: A preparation method of polyaniline gel coated tin copper nanotube composite Granted publication date: 20190719 License type: Common License Record date: 20240408 |
|
| EE01 | Entry into force of recordation of patent licensing contract |